Protection by Aspirin against Experimentally Induced Arterial Thrombosis in Dogs - Danese, C. A; Voleti, Ch D.; Weiss, H. J (Thrombosis and Haemostasis, 1971)
The possible anti-thrombotic properties of drugs which interfere with platelet aggregation were studied. Segments of the peripheral arteries of dogs were isolated, injured either by endarterectomy or chemically by instillation of 0.1 N H2 S04 (chemical injury). Two days later, the segments were examined for the presence of thrombosis. In animals which received only a placebo, 29% of the chemically-injured segments and 43% of the endarterectomized segments became totally occluded with thrombi. Treatment with aspirin (600 mg per day) reduced this incidence to 2 and 11% respectively (p < .05) while treatment with dipyridamole (DPM) (200 mg per day) had no effect. In a second study, aspirin ingestion reduced the incidence of total occlusion in chemically-injured segments from 38 to 0%. Connective-tissue induced platelet aggregation decreased in aspirin treated animals, while DPM had no effect. The findings support previous suggestions that aspirin, perhaps by inhibiting platelet aggregation, has anti-thrombotic properties.